2022
DOI: 10.3389/fimmu.2022.885896
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circNUP214 Modulates the T Helper 17 Cell Response in Patients With Rheumatoid Arthritis

Abstract: Circular RNAs (circRNAs) are important transcriptional regulators of genome expression that participate in the pathogenesis of human diseases. Mechanistically, circRNAs, as competitive endogenous RNAs (ceRNAs), can sponge microRNAs (miRNAs) with miRNA response elements. A previous study identified that hsa_circ_0089172 (circNUP214) is abnormally expressed in Hashimoto’s thyroiditis. However, the role of circNUP214 in rheumatoid arthritis (RA) remains unclear. In total, 28 RA patients and 28 healthy controls we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…CircRNAs act as ceRNAs in various cell types associated with RA, including macrophages, helper T cells, chondrocytes, fibroblast-like synoviocyte (FLS), and others, and fibroblast-like synoviocytes are the primary focus of research in this context ( Table 7 ). For example, CircRNA_09505 can promote AKT1 expression by acting as a miR-6089 sponge through the IκBα/NF-κB signaling pathway in macrophages, resulting in increased the production of TNF-α, IL-6, and IL-12, which cause joint inflammation and joint damage ( 77 ); CircNUP214 functioned as a miR-125a-3p sponge in RA, which promotes the expression of IL-17A and IL-23R in PBMCs and increases the proportion of Th17 cells, resulting in immune dysregulation and inflammatory responses ( 92 ); CircFADS2 promotes the expression of type II collagen, MMP-13, COX-2, and IL-6 via miR-498/mTOR axis, which leads to extracellular matrix (ECM) degradation, inflammation, and cell apoptosis in chondrocytes ( 72 ); Circ-PTTG1IP can promote TLR4 expression by acting as a miR-671-5p sponge, promoting the proliferation, migration, invasion and inflammatory response of FLSs in RA ( 89 ).…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs act as ceRNAs in various cell types associated with RA, including macrophages, helper T cells, chondrocytes, fibroblast-like synoviocyte (FLS), and others, and fibroblast-like synoviocytes are the primary focus of research in this context ( Table 7 ). For example, CircRNA_09505 can promote AKT1 expression by acting as a miR-6089 sponge through the IκBα/NF-κB signaling pathway in macrophages, resulting in increased the production of TNF-α, IL-6, and IL-12, which cause joint inflammation and joint damage ( 77 ); CircNUP214 functioned as a miR-125a-3p sponge in RA, which promotes the expression of IL-17A and IL-23R in PBMCs and increases the proportion of Th17 cells, resulting in immune dysregulation and inflammatory responses ( 92 ); CircFADS2 promotes the expression of type II collagen, MMP-13, COX-2, and IL-6 via miR-498/mTOR axis, which leads to extracellular matrix (ECM) degradation, inflammation, and cell apoptosis in chondrocytes ( 72 ); Circ-PTTG1IP can promote TLR4 expression by acting as a miR-671-5p sponge, promoting the proliferation, migration, invasion and inflammatory response of FLSs in RA ( 89 ).…”
Section: Discussionmentioning
confidence: 99%
“…50 Simultaneously, circNUP214 transcript levels were positively correlated with serum anti-cyclic citrullinated peptide antibody levels in patients with RA. 50 Gao et al demonstrated that plasma circ_0000175 and circ_0044235 expression levels correlated with disease activity and severity in RA. 51 This evidence suggests that specific circRNAs have potential as diagnostic biomarkers for RA.…”
Section: Circul Ar Rna S In Rheumatoid Arthritismentioning
confidence: 93%
“…Peng et al reported that circNUP214 could act as a sponge for miR‐125a‐3p, regulating the transcript levels of IL‐23 receptors in the PBMCs of patients with RA to promote the expression of the pro‐inflammatory factor IL‐17A 50 . Simultaneously, circNUP214 transcript levels were positively correlated with serum anti‐cyclic citrullinated peptide antibody levels in patients with RA 50 . Gao et al demonstrated that plasma circ_0000175 and circ_0044235 expression levels correlated with disease activity and severity in RA 51 .…”
Section: Circular Rnas In Rheumatoid Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…Among ceRNAs are pseudogenes, lncRNAs, or circular RNAs (circRNAs), such as phosphatase and tensin homolog pseudogene 1 (PTENP1), X inactive specific transcript (XIST), or circular RNA sponge for miR-7 (ciRS-7) [155][156][157]. The function of ceRNAs has been studied in diseases like RA, where molecules like protein tyrosine phosphatase non-receptor type 22 (PTPN22) [158], nuclear paraspeckle assembly transcript 1 (NEAT1) [159,160], P38 inhibited cutaneous squamous cell carcinoma associated lincRNA (PICSAR) [161], or circular RNA nucleoporin 214 (circ-NUP214) [162] can modulate miRNA expression. In fact, these interactions can regulate the function of certain genes, either improving or exacerbating RA symptoms as seen in Table 1.…”
Section: Possible Implications In Patients With Ramentioning
confidence: 99%